Educational transformation - Hashim, Rosnani; Zubairi, Ainol Madziah; Abd Rashid, Adnan; Othman, Azam; Siraje Abdallah, Ssekamanya; Hussien, Suhailah; Hassan @ Mohamed, Nor Jana; Abd Karim, Aishah Hanim; Ismail, Halim; Mohamad Jamil, Siti Nurnadilla; Md Sidek, Suzana Suhailawaty (Centre for Islamisation (CENTRIS), IIUM, 2025)
To the true Believers, it is the future of ultimate well-being and true happiness in eternal life with the Divine Pleasure (Riḍwān Allāh) that they are looking forward to. This ultimate goal is not to be achieved by renouncing the world or by abondoning worldly and societal responsibilities. On the contrary, the Ummah of Believers has to fulfil its active stewardship (khilāfah) and leadership (imāmah) role of developing and nurturing the world and human civilisation. These are to be constructed on the foundations of Revealed Knowledge as ends and the scientific knowledge of the secrets of nature (as “signs” of Allah) as means. The latter must be ethically utilised and competently harnessed as means for the proper advancement and holistic progress of human and environmental well-beings—in conformity with the Maqāṣid al-Sharī`ah, the Qur’anic vision of the good life (ḥayāh ṭayyibah) and the vision of “a good land with a Forgiving Lord” (baldatun ṭayyibatun wa Rabbun Ghafūr) (see Q. Saba’, 34 : 15).